L’autoritarisme et la Liberté Positive de Personnage Principal dans le Roman Sans Famille d’Hector Malot (Une Etude Psychologie d’Erich Fromm) (Universitas Negeri Semarang, 2020)
The focus of this study is the authoritarianism and positive freedom on the main character in the novel Sans Famille. The theory in this study used humanistic psychology of Erich Fromm. The aim of this study is to find out and to describe the existence of the main character in the novel. Data of this study is the novel Sans Famille by Hector Malot. The method of the study is the qualitative descriptive method. Data analysis in this study in three pieces: The authoritarianism on the main character; the positive freedom on the main character, relation between of the authoritarianism and positive freedom on the main character.